2019
DOI: 10.1177/0363546519888467
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With an Increased Risk of Recurrence After a First-Time Patellar Dislocation: A Systematic Review and Meta-analysis

Abstract: Background: Recurrent dislocations after a first-time lateral patellar dislocation may occur in more than 50% of patients and can cause long-term disability. Many factors have been suggested to influence the risk of recurrence. Purpose: To systematically review and quantitatively synthesize the literature for factors associated with an increased risk of recurrence after a first-time patellar dislocation. Study Design: Systematic review and meta-analysis of observational studies. Methods: A total of 4 electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 33 publications
5
92
2
4
Order By: Relevance
“…A meta-analysis compared the difference of redislocation between mild and severe trochlear abnormity, based on Dejour's classification of trochlear dysplasia, and found that the probability of recurrent patellar dislocation in severe trochlear dysplasia was 1.41 times higher than that in mild cases, and the probability of recurrent patellar dislocation in patients with femoral trochlear dysplasia is 4.15 times higher than that in people with normal trochlear development. These results further confirmed the value of femoral trochlear dysplasia in predicting recurrent patellar dislocation [1]. However, the relationship between sulcus angle and recurrent patellar dislocation was not shown in this meta-analysis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A meta-analysis compared the difference of redislocation between mild and severe trochlear abnormity, based on Dejour's classification of trochlear dysplasia, and found that the probability of recurrent patellar dislocation in severe trochlear dysplasia was 1.41 times higher than that in mild cases, and the probability of recurrent patellar dislocation in patients with femoral trochlear dysplasia is 4.15 times higher than that in people with normal trochlear development. These results further confirmed the value of femoral trochlear dysplasia in predicting recurrent patellar dislocation [1]. However, the relationship between sulcus angle and recurrent patellar dislocation was not shown in this meta-analysis.…”
Section: Discussionsupporting
confidence: 78%
“…Patellar dislocation is a common traumatic disease, with the incidence of primary patellar dislocation in the population being 23-42 per 100,000 per year. The probability of recurrent dislocation in these patients after conservative treatment is 17-66%, and the younger the patient, the higher the probability of recurrence [1][2][3][4][5]. It is believed that patellar dislocation is a multifactorial disease with the combined effects of bone anatomical abnormality and abnormality in the soft tissue structure that maintains the stability of the patellofemoral joint.…”
Section: Introductionmentioning
confidence: 99%
“…The included studies had variations in the de nitions of risk factors; patella alta de ned with CD ratios ranging from >1.2 to 1.45, and IS ratio >1.2 to 1.3; and elevated TT-TG distance ranging from >14 to 20 mm. Based on the above risk factors, they reported a recurrence risk of 7.7-13.8% with no abnormal risk factors, 29.6-60.2% with 2 abnormal risk factors, and 70.4-78.5% with 3 abnormal risk factors present[15]. A majority of our patient had 2 or more abnormal risk factors (69.7%), and 11 patients (33.3%) had at least 3 risk factors.…”
mentioning
confidence: 45%
“…The risk factors we chose for our cohort were the predictive factors for recurrence identi ed in the metaanalysis by Huntington et al [15]. This represents the latest meta-analysis to study factors associated with the risk of recurrence for patella dislocations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation